Scientific and legal conclusion as an instrument for solving issues in the legal sphere of the land management industry - Dorosh, Y; Ibatullin, S; Avramchuk, B; Kharytonenko, R; Patiyuk, O (Land Management, Cadastre and Land Monitoring, 2019)
The necessity of attracting scientific and practical conclusions to resolve controversial issues in the land management industry is substantiated. The practical experience of applying the scientific and practical conclusion and conducting scientific research in solving the problem associated with the correction of technical errors in the state land cadastre is considered.The analysis and justifiably technical error in the data of the State Land Cadastre on the change in the purpose of the land for the construction and maintenance of an apartment building from erroneous purpose for conducting agricultural production was carried out.The list of documents that must be submitted together with the application to the cadastral registrar on making amendments based on a technical error of information about the land registered in the State Land Cadastre is given.It is noted that it is necessary to start the practice of creating scientific and legal conclusions to resolve controversial and complex issues in land management with the involvement of leading scientists in the industry and specialized research institutions.Key words: scientific and legal opinion, state land cadastre, purpose, public cadastral map, correction of errors in the conduct of the SLC.